2017
DOI: 10.1002/prp2.287
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on intestinal bile acid transport in C57BL/6 mice

Abstract: Intestinal and hepatic bile acid transporters are important for enterohepatic bile acid circulation and pharmacokinetics. Based on previous literature, we hypothesized that the expression of bile acid transporters and intestinal bile acid absorption are lower in older individuals. Here, we measured active taurocholate absorption across the ileum of male C57BL/6 mice in two different age cohorts – young (age range of 89–224 days) and old (age range of 613–953 days). Also examined in these mice were mRNA express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Alteration in intestinal BA transport is closely related to expressional changes in BA transporters. Gao et al (2017) showed that aged mice have less ASBT and taurocholate transport in the ileum. Zhu et al (2017a) found consumption of modified pectin downregulate FABP6 and OSTα/β to inhibit absorption of BAs in the ileum.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration in intestinal BA transport is closely related to expressional changes in BA transporters. Gao et al (2017) showed that aged mice have less ASBT and taurocholate transport in the ileum. Zhu et al (2017a) found consumption of modified pectin downregulate FABP6 and OSTα/β to inhibit absorption of BAs in the ileum.…”
Section: Introductionmentioning
confidence: 99%
“…As was consistent with human studies, the reabsorption of BA in the ileum of aging mice was similarly reduced, with about a 50% lower absorption of taurocholate than in younger mice. This was supported by the reduced gene expression of apical sodiumdependent bile acid transporter (Asbt), which is the key transporter regulating BA uptake in the intestinal apical membrane [27]. These observations suggest that the decreased expression of Asbt potentially acts as a rate-determining step in BA reabsorption.…”
Section: Pancreatic Function Declines With Age Due To Decreased Pancr...mentioning
confidence: 95%
“…The age-related decreases in BA synthesis and their potential impact on cholesterol utilization are closely linked to the observed disturbances in the enterohepatic circulation of BAs during aging, which are evidenced by the reduced intestinal reabsorption and liver transport of the BAs. Aging was associated with the decreased mRNA expression of the intestinal BAs reabsorption transporter Asbt [27]. The mRNA expressions of the liver BA uptake transporters Na+/taurocholate cotransporting polypeptide (Ntcp) and organic anion transporting polypeptide 1b2 (Oatp1b2) were decreased during aging, whereas the expression of the BAs efflux transporter Bsep remained unchanged in aging mice [27,89].…”
Section: Bile Acid Enterohepatic Circulation and Lipoprotein Dynamics...mentioning
confidence: 99%
“…While it is clear that ASBT expression is enhanced after weaning, there is also evidence that aging decreases intestinal bile acid absorption. Studies by Gao et al demonstrated that 3 H-TC uptake across ileum in Ussing chambers was reduced approximately 50% in a cohort of aged ~2-year-old) C57BL/6 mice relative to a younger (<1-year-old) cohort (133). There was a corresponding approximately 50% decrease in ASBT mRNA expression in the older cohort, suggesting that decreased ASBT expression in old age may be responsible for the reduced bile acid absorption in these mice.…”
Section: Asbt Ontogeny and Agingmentioning
confidence: 97%